Job Opportunities for the Disabled Labor Forces: Review of Legal Awareness and Protection - Ibrahim, Maulana; Wulandari, Poppy; Maria Laot Kian, Antonius (The Center for Disability Studies and Services Brawijaya University, 2025)
The enhancement of the quality of life for all individuals is an imperative component of societal advancement. This is a principle that pertains to the disabled population as a particularly vulnerable group. In Indonesia, the estimated number of disabled labourers is projected to reach 720,748 in 2022. Despite this figure having increased by 160.18% since 2021, it is anticipated that the involvement of people with disabilities in the formal sector will remain low until 2023. The objective of this research is twofold: firstly, to analyse the extent of legal awareness and protection for disabled workers, and secondly, to determine a solution for the discrepancy between legal provisions and awareness about employment opportunities for disabled workers. In order to analyse these gaps and formulate solutions to the identified problems, this research employs a qualitative research design that utilises a normative juridical approach. Despite the existence of legal provisions in Indonesia to support the United Nations' disability inclusion strategy, empirical evidence indicates that legal awareness and protection remain inadequate. It is anticipated that the government will not only formulate legal instruments to safeguard the rights of disabled individuals but will also oversee the employment of disabled individuals within both governmental and private sector organisations.